THE USE OF EXTENSIVE READING IN TEACHING READING - Raihani Ferdila (Journal of English and Education, 2014)
The study investigates benefits of using extensive reading in teaching reading and as well as students’ attitudes toward it. A case study design as a part of qualitative research was employed in this study. The data were collected through classroom observation, questionnaire and interview. The participants of this study were a class of second graders in one of the public junior high schools in Bandung. The findings reveal that extensive reading was beneficial in teaching reading. There are five benefits found, those are building students’ perspective that reading is a fascinating activity, creating enjoyable learning atmosphere, helping students in developing a wide vocabulary, improving students’ reading comprehension, and increasing students’ motivation in reading. In addition, most students had positive attitudes toward the use of extensive reading in their reading class. Based on the findings, it is expected to contribute to the teaching of English especially in the use extensive reading technique in teaching reading. However, in order to achieve maximum benefits of the technique, it is suggested that some aspects of the technique should be improved; these include the improvement of teacher’s understanding of the principles and concepts of extensive reading, the insight of the importance of giving clear instructions, and the awareness of designing various activities.